Społeczna odpowiedzialność przedsiębiorstw wobec pracowników - Nowak-Lewandowska, Renata (Corporate Social Responsibility Towards Employees, 2009)
Enterprises in Poland attach more importance to principles of social responsibility. It is reflected in taking care of their most valuable assets, i.e. employees. The part of entrepreneurs sharing the market are convinced of measurable benefits of this attitude, some part of them need the time to become aware of responsible treatment towards employees. The aim of this article is the presentation of the importance of corporate social responsibility towards employees and the presentation of good practices in this field.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 42, s. 157-167